Enzymic hydrolysis of myelin basic protein and other proteins in central nervous system and lymphoid tissues from normal and demyelinating rats. - Buletza, G F (1976)
Proteolytic activity of central-nervous-system tissue of the normal rat was examined over the pH range 2-9 with casein, haemoglobin and myelin basic protein as substrates. With casein as a substrate, brain and spinal cord homogenates showed very similar activity profiles with increasing pH, with the main peaks of proteolytic activity at pH 3-4 and 5-6. When haemoglobin was used, one broad main peak of activity from pH 3 to 5 was demonstrated. There was no optimum pH, however, for proteolytic activity with myelin basic protein as a substrate, and considerable hydrolysis were observed from pH 3.5 up to pH8. Proteolytic activity at the various pH values was compared by using homogenates of spinal cords from rats with acute experimental allergic encephalomyelitis and those from rats injected with Freund's adjuvant alone. The profiles of activity were similar with peaks at pH 3.5 and 5.5 with casein as a substrate, but the specific activity was significantly higher at most pH values in the spinal-cord homogenates from rats with experimental allergic encephalomyelitis. Similarly the spinal-cord homogenates from these latter rats contained much more proteolytic activity toward myelin basic protein throughout the pH range than was present in the control spinal cords. Homogenates from lymph nodes of rats with experimental allergic encephalomyelitis and from those of the controls contained two to three times as much proteolytic activity as that of the central-nervous-system tissue and had a different proteolytic activity profile form that of the central-nervous system, with higher activity at the neutral than at acid pH. The results are discussed with regard to the probability that inflammatory cells such as lymphocytes may be the cause of the increased proteolytic activity in the central nervous system of animals with experimental allergic encephalomyelitis, and that enzymes from these cells possess the capability of digesting myelin basic protein.